Potential concerns and challenges toward anti-SAR-CoV-2 vaccine among undergraduate students of North India - Mishra, Rakhi; Lata, Hem; Sonia; Kumar, Santosh; Devi, Seeta (International Journal of Basic & Clinical Pharmacology, 2025)
Background: SARS-CoV-2 has trampled the healthcare system during the pandemic and still frames distressed pictures of quarantine, isolation, and vaccine hesitancy. Hence, the present study was conducted at a tertiary care hospital in Uttarakhand to address the paucity of data regarding concerns and challenges in accepting the anti-SAR-CoV-2 vaccine among medical and nursing students. Methods: An online survey was conducted via the Google platform using Google forms. A total of 248 undergraduate medical and nursing students who were selected via the non-probability. Results: The mean age was 22.0±3.6 years. Of them, 58% were B.Sc. nursing students, and 42% were MBBS/DNB students. About 85% agreed that the COVID-19 vaccine was safe and were psychologically prepared for minor signs and symptoms after vaccination. About 23% were worried about the hormonal changes that may occur after getting vaccinated. Nearly one third (37%) had concerns about hospital admission and expenses in case of any adverse events. Overall, 56% had accepted the SARS-CoV-2 vaccine. Conclusions: Although the acceptance rate was high among participants, a few concerns and challenges reported by participants cannot be overlooked. Hence, there is a need to continuously address the concerns to improve the rate of adherence and to further psychologically prepared for the minor signs and symptoms after vaccination SARS-CoV-2.